Instagram’s Usage on Spreading Awareness in Politics Among Youth During Demonstration - Adilah, Kezya Putri; Rahmawan, Detta; Wibowo, Kunto Adi (Universitas Dian Nuswantoro, 2026)
The ever growing usage of Instagram among youths and its role in the dissemination of political information is the main focus of this research. This study aims to answer the following question: How does Instagram usage, exposure to political content and feature usage influence political awareness and indirect political participation among youth during political demonstration? This research uses a quantitative approach with a survey method. The data was collected from 120 undergraduate students from Padjadjaran University who are active users of Instagram and was analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The results of this research showed that exposure to political content on Instagram has a significant influence towards indirect political participation, such as spreading political awareness. On the other hand, Instagram usage intensity and the feature usage of Instagram did not show a significant influence on political awareness nor indirect political participation. These findings indicate that youths’ political engagement on social media is more influenced by the content that they encounter compared to the frequency of the platform usage itself. Therefore, this research highlights the importance of the political content’s role in encouraging indirect political participation among youths through social media.Keywords: Instagram; Social media; Political awareness; Political participation